Capacity planning method for resource consolidation in mass cloud web hosting - Chyzhov, O.; Fesenko, A. (Problems of Informatization and Management, 2025)
In this scientific article, a capacity planning method is proposed for resource consolidation in the mass cloud web hosting segment, based on mathematical modeling of aggregated stochastic loads and queueing theory. The method optimizes the allocation of RAM for low-traffic resources by consolidating traffic into a single computing pool while strictly maintaining the target reliability level (SLA 99.9%). Through simulation of the system’s weekly operating cycle, it is shown that the proposed method provides an integrated resource saving of 16%, mitigates the impact of stochastic load peaks, and reduces the provider’s operational costs without degrading service quality.